Optimasi Hidraulik Penanganan Gerusan di Hilir Bendung - James Zulfan (JURNAL TEKNIK HIDRAULIK, 2017)
Scouring issues which occured at downstream of a weir can potentially endangers the weirs structureif the hydraulic jump is not properly dissipated, especially when the downstream river bed is unprotected. Due to strong correlation between discharge and the depth of the scour emerge, downstream protection is needed to maintain structure stability. To solve this problem, heavy protection is set at downstream of the weir such as riprap to prevent the scouring. This study aims to review the effectiveness of 3 alternatives measures through 3 dimensional physical model test by assessing the correlation among hydraulic parameters and the depth of the scour. The experiment were performed at hydraulic laboratory with a case study of Rengrang Weir in West Java. Based on laboratory test, hydraulic measures are effective to reduce the impact of the scouring. Alternative measures with riprap is more preferably because the easiness, economic and availability of thematerialon site.